Two new species of the spider genus Tropizodium Jocqué & Churchill, 2005 with notes on the femoral organ clade from Southeast Asia (Araneae, Zodariidae, Zodariinae) - Dankittipakul, Pakawin; Jocqué, Rudy; Singtripop, Tippawan (Zootaxa, 2012)
Four species of Tropizodium Jocqué & Churchill, 2005 are newly recognized from Southeast Asia of which two speciesare new: T. siam sp. nov. from northern Thailand and T. murphyorum sp. nov. from Bali, Indonesia. Tropizodium serrafer-um (Lin & Li, 2009) comb. nov. is here transferred from Zodariellum Andreeva & Tyschchenko, 1968. The monotypicgenus, Indozodion Ovtchinnikov, 2006, is considered a junior synonym of Tropizodium. Its single species consequently becomes Tropizodium inayatullahi (Ovtchinnikov, 2006) comb. nov.